Physiological responses of wheat plant to salinity under different concentrations of Zn - Abedini, Masoumeh (Acta Biologica Szegediensis, 2016)
In this study, the effects of different concentrations of Zn (1 and 5 μM) on wheat plants were investigated hydroponically at two levels of salinity (50 and 100 mM). High salinity, at both concentrations of Zn, significantly decreased the plant’s growth and photosynthetic pigments and protein contents, while increased the membrane permeability, as well as the proline, H2O2 and MDH contents. The activities of antioxidant enzymes were not affected by high salinity at low concentration of Zn, but increased significantly at high concentration of Zn. Low salinity, at both levels of Zn, significantly increased the proline and H2O2 contents of plants and antioxidant enzymes activities, but did not significantly affect the other studied parameters. There was no significant difference in the studied parameters between plants supplied with two concentrations of Zn at 50 mM NaCl. On the contrary, at 100 mM NaCl, application of high concentration of Zn, significantly alleviated the injurious effects of salt stress by inducing antioxidant enzymes.